Complete pathological response following neoadjuvant FOLFIRINOX in borderline resectable pancreatic cancer - a case report and review. Issue 1 (December 2016) - Gostimir, Mišo; Bennett, Sean; Moyana, Terence; Sekhon, Harman; Martel, Guillaume
Abstract Background Pancreatic cancer is among the top 5 most common cancers worldwide, but is particularly devastating due to its insidious nature. Complete surgical resection remains the only potential curative treatment, although only 20 % of patients present with a resectable tumor. Patients may alternatively present with borderline resectable pancreatic cancer or locally advanced pancreatic cancer and can be offered treatment with neoadjuvant intent. The effectiveness of these treatments is unclear and there is a paucity of data to suggest one optimal treatment approach. Case presentation We describe a 61-year-old female who presented with a two-week history of obstructive jaundice in the context of vague abdominal pain that had been ongoing for years prior to her visit. CT scan of the abdomen confirmed a hypovascular mass in the uncinate process consistent with borderline resectable pancreatic cancer. Pancreatic adenocarcinoma was confirmed with endoscopic ultrasound guided fine-needle aspiration cytology. Following multidisciplinary discussion, it was recommended that she undergo treatment with FOLFIRINOX. After a total of 13 cycles, follow up CT revealed that the lesion had decreased in size and she was offered resection as a potentially curative treatment. She underwent pancreaticoduodenectomy. Final pathology report revealed no evidence of residual adenocarcinoma (ypT0 ypN0 (0/23)). The patient remains disease-free 15 months following surgery. Conclusion To date, there have been very few reports of a complete pathological response following neoadjuvant therapy in borderline resectable or locally advanced pancreatic cancer. This report describes a unique case of a complete pathological remission in a patient with borderline resectable pancreatic cancer following FOLFIRINOX therapy alone and adds to the growing base of evidence meriting the initiation of clinical trials to assess the efficacy of FOLFIRINOX in these subsets of pancreatic cancer.